Identification of candidate genes associated with resistance against race 0 of Colletotrichum lentis in Lens ervoides - P. K. Bawa; J. Halliday; K. Kapoor; S. Banniza (Scientific Reports, 2022)
Abstract Resistance to anthracnose caused by the fungal pathogen Colletotrichum lentis was explored through transcriptome sequencing over a period of 24 to 96 h post-inoculation (hpi) of the partially resistant recombinant inbred lines (RIL) LR-66-528 and susceptible LR-66-524 of the crop wild relative Lens ervoides population LR-66. The development of infection vesicles and primary hyphae by C. lentis were significantly higher on susceptible RIL LR-66-524 compared to partially resistant LR-66-528 at 24 and 48 hpi, but exponential trends in fungal growth were observed between 24 to 96 hpi in both RILs. Comparison of inoculated with mock-inoculated samples revealed 3091 disease responsive genes, among which 477 were differentially expressed between the two RILs. These were clustered into six expression clusters with genes that had either high or low expression in one of the RILs. Differentially expressed genes (DEGs) were functionally annotated and included genes coding LRR and NB-ARC domain disease resistance proteins, protein detoxification, LRR receptor-like kinase family proteins, and wall-associated Ser/Thr Kinases. DEGs were compared to genes in previously published anthracnose resistance QTLs mapped in LR-66 and revealed 22 DEGs located in 3 QTLs. Expression of 21 DEGs was validated using RT-qPCR confirming expression trends in RNA-seq.